2021
DOI: 10.1038/s41598-021-85401-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of deep inspiration breath hold on prone photon or proton irradiation of breast and regional lymph nodes

Abstract: We report on a comparative dosimetrical study between deep inspiration breath hold (DIBH) and shallow breathing (SB) in prone crawl position for photon and proton radiotherapy of whole breast (WB) and locoregional lymph node regions, including the internal mammary chain (LN_MI). We investigate the dosimetrical effects of DIBH in prone crawl position on organs-at-risk for both photon and proton plans. For each modality, we further estimate the effects of lung and heart doses on the mortality risks of different … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 42 publications
4
22
0
Order By: Relevance
“…A recent meta-analysis by Lai et al even hinted that the combined use of prone positioning and breathholding seemed the most promising to decrease cardiopulmonary exposure, rather than breathholding or prone positioning on their own 15 . In our previous research, we showed a benefit of prone positioning over supine positioning in WB + RNI 9 , 12 , and in another paper that the addition of breathhold for WB + RNI in prone position was more beneficial than prone positioning alone in photon beam treatment 16 . But contrary to the breast itself in prone position 14 , nodal target volume locations may vary significantly between shallow breathing and breathhold, requiring strict breathhold monitoring to avoid missing the target.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…A recent meta-analysis by Lai et al even hinted that the combined use of prone positioning and breathholding seemed the most promising to decrease cardiopulmonary exposure, rather than breathholding or prone positioning on their own 15 . In our previous research, we showed a benefit of prone positioning over supine positioning in WB + RNI 9 , 12 , and in another paper that the addition of breathhold for WB + RNI in prone position was more beneficial than prone positioning alone in photon beam treatment 16 . But contrary to the breast itself in prone position 14 , nodal target volume locations may vary significantly between shallow breathing and breathhold, requiring strict breathhold monitoring to avoid missing the target.…”
Section: Introductionmentioning
confidence: 84%
“…The RBH manoeuvre was monitored using 2 Respisens magnetic sensors (Nomics, Angleur, Belgium) placed on the breast couch and thoracic wall 20 . Patient position and sensor placement is illustrated in a figure in the publication by Speleers et al 16 No IV-contrast was administered. This provided us with a set of 3 scans of distinct clinical situations for each patient, namely BH, RBH and free breathing, which for further purposes of this publication we will call failure to breathhold (FTBH).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A dosimetric study would be incomplete without a display of dose-volume histograms. Modern radiotherapy planning optimization processes deal with small dose differences, of the order of a few percentage points 41 . We strived to attain graphical integrity, visualizing small differences without undue distortion.…”
Section: Discussionmentioning
confidence: 99%
“…Early radiation pneumonitis is detectable on follow-up CT 1–3 months after breast cancer radiotherapy 45 . In a photon-proton collaborative study of patients at high risk of breast cancer recurrence, radiobiological modeling estimated the thirty-year mortality rates from radiotherapy-related cardiac injury and lung cancer at 1.66% to 4.03% 41 , although these rates did not outweigh the ~ 8% disease-specific survival benefit of radiotherapy. In a study estimating lung cancer and cardiovascular mortality among female breast cancer patients receiving radiotherapy, the risks were shown to increase with lung and heart dose, even in non-smokers without familial or cardiac history 46 .…”
Section: Discussionmentioning
confidence: 99%